Optimization of near-field scattering dielectric probe - Lim, Wei Wen (2010)
This final year project report studies the parameters for the design of the scattering dielectric probe which consist of the metal coating used, type of mode used for the laser source and the geometry of the detector so as to find the optimal results for these parameters. The approach of the report is to first focus on the fundamental and principle of Scanning Near-field Optical Microscopy (SNOM) and some important components and process related to the SNOM system such as the fabrication methods for the SNOM's probe, type of probe used, metal coating used for SNOM's probe and the characteristics of the optic fiber. Next simulation software Rsoft FullWAVE will be used simulation designed probe based on the different parameters such as the different tapered angle, different metallic coating and different transmission mode for the source. Last but not least performing experiments to analysis the resolution of the image obtained from the experiments for both the AFM and SNOM image. These images obtained by the fabricated probe with different tip diameters. This will also conclude the relationship between the tip diameter and resolution of the images. From the simulation, the result for gold is more consistent than that of silver and the mode of operation used was found to be HE11 which produces small spot size compared to that of TM01. As for the experimental results, it was found that the smaller the tip diameter the better the resolution of the image obtained for both the topography and optical information. These results obtained will better improve the setup of the SNOM system and the further improve the probe's efficiency to detect the near-field signal on the sample surface so as to provide clear and sharp images of the topography and optical information of the desired sample.